Exploring the pre-service basic science teachers’ misconceptions using the six-tier diagnostic test - Muhamad Imaduddin; Muhammad Mujahidus Shofa; Muhammad Fatkhur Riza; Achmad Ali Fikri (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study explored the pre-service basic science teachers’ misconceptions using a six-tier diagnostic (STD) test. This study used a cross-sectional survey research model with respondents, namely pre-service basic science teachers (PBSTs) who are first-year students. The six-tier diagnostic test consisted of three questions about change in matter (CIM), classification of matter (COM), and separation of mixtures (SOM). Each test package consists of six questions ranging from questions at the macroscopic level, microscopic communication, level of confidence, symbolic visualization to represent microscopic conditions, and self-confidence in representing concepts. The combination of answers and decisions in six-tier diagnostic includes scientific conception (SC), almost scientific conception (ASC), lack of confidence (LC), lack of knowledge (LK), misconception (MSC), have no conception (HNC). The study showed that the conceptual mastery condition is dominated by the misconceptions (MSC) category. The condition for pre-service basic science teachers’ mastery concepts having the most scientific conception category is related to changes in matter (CIM), while the condition that shows the least scientific conception category is related to material classification (COM). The results can map the conditions of mastery of the pre-service basic science teachers’ concept so that strategies can be designed to correct the emerging misconceptions.